Laporan Kasus : Trauma Tumpul Kepala Akibat Jatuh dari Ketinggian - Alya Rananda RH; Farah Primadani K; Ferryal Basbeth (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Introduction: Falls from height are a major cause of high-energy blunt trauma, frequently resulting in severe head injury and death. In forensic medicine, analysis of head injury patterns is essential to determine the mechanism and manner of death. Objective: To report and analyze a fatal case of severe head injury due to a fall from height based on forensic examination findings and relevant literature. Case report: A male adolescent was found deceased after an alleged fall from the third floor of the mosque building. Forensic examination revealed a depressed skull fracture, dural tear, extensive intracranial hemorrhage, and multiple associated injuries. Discussion: The head injury pattern indicates high-energy blunt force trauma. Associated thoracic and bilateral femoral fractures support a vertical fall mechanism. These findings are consistent with previously reported fatal free-fall cases. Conclusion: Death was caused by severe blunt head trauma resulting from a fall from height, leading to increased intracranial pressure and brainstem failure.